Estimation of Indonesian Male Life Table with Survivorship Probability Method in Smoothed Way by using Coale-Demeny’s Life Table - Hanifah Dara Puspita; Nurul Huda Prasetya; Ismail Husein (ZERO: Jurnal Sains, Matematika dan Terapan, 2020)
The population of Indonesia in each province are continuing increased every year. The total population of Indonesia in 2010 was 237.641.326, while in 2010 it increased by 32.562.591 people to 270.203.917 people, with the male population are greater than women population. By the population of Open Unemployment Male Rate (TPT) is higher than female, which is 5.31 percent compared to 5.23 percent. Unemployment is one of the ten important events in triggering stress. The male who don't have a job get a higher stress level then female, it found that the male who were unemployed were more risk towards death than female, about 78 percent compared to 37 percent. The purpose of this study is to estimate the life table of Indonesian male population by smoothing it using the Coale-Demeny’s life table based on the 2010 and 2020 Population Census data. The method of this study is Survival Analysis in Smoothed Way by using Coale-Demeny’s Life Table. The result of this study obtained by 58,84 years life expentacy (AHH), means that from 100.000 babies born will be able to live to the age of 58 or 59 years. By the pattern of the number of Indonesian male residents who survive, the result is close to (has similarities) to the pattern of the number of Indonesian male residents who survive that produced by the Central Statistics Agency (BPS-Statistics Indonesia).